Formulation of anomerization and protonation in d-glucosamine, based on 1H NMR. (April 2020) - Virués, Claudia; Hernández, Javier; Higuera-Ciapara, Inocencio; Martínez-Benavidez, Evelin; Olivares-Romero, J.Luis; Navarro, Rosa Elena; Inoue, Motomichi
Abstract: The major anomer of non-protonated neutral d -glucosamine GlcN 0 is the β-form, while the α-anomer is dominant for protonated cationic glucosamine GlcNH + . The present work confirmed correlation between the anomerization and the protonation by simultaneous determination of signal intensity and chemical shift in pD-variation 1 H NMR, and formulated the equilibrium constants between subspecies α-GlcN 0, β-GlcN 0, α-GlcND +, and β-GlcND + to interpret the correlation. The individual anomerization constants, K an  = [βGlcN]/[αGlcN] and K anD  = [βGlcND + ]/[αGlcND + ], are linked to each other through the relation K Dα ∙ K anD  =  K Dβ ∙ K an with the deuteration constants K D α and K D β of the anomers. The anomer populations are stimulated by OD − and D + ions in the dose−response form. The acidic deuteron in α-GlcND + is populated mostly at the nitrogen atom, whereas the population in β-GlcND + is comparable at nitrogen and anomeric oxygen; this difference is consistent with the basicity of the nitrogen and the anomerization process of glucosamine. Graphical abstract: Image 1 Highlights: Anomerization is correlated to protonation. Anomer populations are defined by protonation constants. Anomerization and protonation are related to basicity of amino group.